Coordinative constructions in Arabic: aspects of morphosyntax as an indicator of interpersonal status - Moutaouakil, Ahmed (ALFA: Revista de Linguística, 2009)
From a FDG point of view, a distinction must be made between two kinds of complexity with quite different indicating devices: interpersonal complexity and structural complexity. As regards interpersonal complexity, verb mood, case marking and interrogative particles are some of the specific morphosyntactic means that Standard Modern Arabic provides to express the status of the interpersonal units in coordinative constructions and the different relationships that can obtain between these units. A general unified approach with some implications for other morphosyntactic areas such as non-restrictive term modifiers is proposed.